An Evolutionary Story of Agency - Moreno, Álvaro; Peretó, Juli (Springer Nature, 2025)
This open access book exposes the role of "agency" in the history of life. Agency is understood as the capacity of an organism to act, make decisions, and exercise control over its actions in order to achieve goals or to navigate and interact with its environment. The question of agency has become a hot and controversial topic in Biology and Philosophy of the Natural Sciences. This volume studies said topic through its historical expressions, investigating how and why it has appeared, and what was its selective advantage in the past, assuming a continuity in how it has evolved in different life forms. By also explaining how and why agency has evolved and become more complex in some branches of the tree of life, the authors show how life has made its way on our planet with forms of agency as diverse as those shown by bacteria, plants or animals, which are the most sophisticated and complex agents. The book is of great interest to a broad audience, whether philosophically or biologically inclined, interested in understanding fundamental aspects of how life works and in seeking explanations for why life has been so successful on planet Earth.